SUNLIGHT DRIVEN PHOTOCATALYTIC DEGRADATION OF 2-CHLOROPHENOL BY POLYPYRROLE/GRAPHENE OXIDE COMPOSITES - Baharin, Siti Nor Atika; Sambasevam, Kavirajaa Pandian; Suhaimi, Nur Farahin; Rahat, Arifutzzaman; Rahman, Saidur; Musiran, Shafira Nadira (Malaysian Journal of Science, 2021)
Polypyrrole/graphene oxide (PPy/GO) was synthesized and evaluated as an effective photocatalyst to degrade 2-chlorophenol from aqueous solution under solar light irradiation. The PPy/GO composite was synthesized by the incorporation of PPy with the GO using Hummer’s method(s). Three different compositions of PPy/GO composites were prepared with the varying ratio of PPy and GO (1:1, 1:4, 9:1). Physicochemical properties of pristine PPy, GO and as synthesized PPy/GO composites were characterized using FTIR, UV-Vis, XRD, and SEM with EDX. The characterizations results revealed that PPy was successfully integrated with the GO in the PPy/GO composites. The photodegradation of 10 ppm of 2-chlorophenol has been observed under sunlight for 3 hours with the exposure contact time of 180 minutes before being tested with UV-Vis in order to obtain the percentage of degradation in the sunlight. The degradation study exhibited that PPy/GO composite with the ratio of 1:1 exhibited the highest percentage of degradation of 71.08 and 68.96 % at the time of 180 minutes and 3 hours respectively.